Correspondence between the Objective and Subjective Economies: The Role of Personal Economic Circumstances. (17th June 2013) - Fraile, Marta; Pardos‐Prado, Sergi
<x xml:space="preserve">Abstract</x> The impact of sociotropic economic satisfaction on the vote has been thoroughly analysed. However, knowledge about how citizens acquire information about the economy and the degree of correspondence between objective macroeconomic changes and citizens' subjective economic perceptions is much more limited. While the effect of partisan rationalisation has recently received some attention, the role of objective personal economic conditions in assessing national economic conditions is still unclear. We suggest that macroeconomic changes have some impact on subjective economic satisfaction, especially among higher‐income and socio‐professional strata with higher risk aversion rates to negative macroeconomic shocks. The results are obtained via three‐level hierarchical linear models using the cumulative file of the European Social Survey (2002–9) and confirm the relevance of citizens' personal economic circumstances as a filter to perceive the state of the economy.